STUDI KASUS TENTANG PESERTA DIDIK YANG BERPERILAKU TIDAK SOPAN TERHADAP GURU - Saragih, Hana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Impolite behavior is the opposite of polite behavior. This impolite behavior includes saying rude things, being disrespectful, disrespectful, and violating school rules and regulations. In general, this research aims to gain knowledge and increase insight by dealing with students who behave disrespectfully towards teachers. The subjects in this research were two students. This research uses descriptive methods and the form of research is a case study. The data collection techniques used were interviews, observation and documentation. The data analysis used is problem identification, diagnosis, prognosis, treatment and evaluation. The counseling model used is the behavioral counseling model. In this study, the characteristics were rude, disrespectful, disrespectful, and violating school rules and regulations. The types in this research are manners towards parents, teachers and friends. Factors in research, internal and external factors. The impact in this research is reduced attention and less respect for teachers.